DAN DIACONESCU: THE POLITICS OF BREAD AND CIRCUSES - VALENTIN QUINTUS NICOLESCU; SABINA BASIUL (Challenges of the Knowledge Society)
Founder and owner of two television stations, Dan Diaconescu found the opportunity to rise the electoral support for his anti-system party through media channels in the circumstances of a tumultuous political year and a bitterly personal power struggle between President Traian Băsescu and Prime Minister Victor Ponta. He described the victory in the upcoming parliamentary elections as a start of the battle against the post-communist Romanian political class that impoverished the country. Through this battle lead by him and other members of his party, his „army of angels”1, Dan Diaconescu says he can liberate the Romanian people and install „people’s dictatorship” that will punish all the political class for the injustices suffered by them. In a context of highly visible and influential populist discourse, this paper considers the self-representation of Dan Diaconescu and his People’s Party – Dan Diaconescu during parliamentary election campaign in 2012. First of all, a multi-methodological approach was adopted to examine the key elements of national populist discourse: antagonistic struggle between politicians and citizens, popular sovereignty, corruption of the political class and popular mobilization for political change. After that, I will examine how this Romanian form of populism represents the rival version of western representative democracy, the populist democracy specific to Latin America based on direct representation embodied by a leader or a party capable to symbolize the power of the people. Within this frame, I will try to analyse to what degree Dan Diaconescu’s populism enrolls in the logic of Latin American populism instead of a cultural or ethnic populism dominant in Europe.